A Nudibranch Marine Extract Selectively Chemosensitizes Colorectal Cancer Cells by Inducing ROS-Mediated Endoplasmic Reticulum Stress - Ruiz-Torres, Verónica; Forsythe, Nicholas; Pérez-Sánchez, Almudena; Van Schaeybroeck, Sandra; Barrajón-Catalán, Enrique; Micol, Vicente (Frontiers in Pharmacology, 2021)
The present study shows the putative antiproliferative mechanism of action of the previously analytically characterized nudibranch extract (Dolabella auricularia, NB) and its different effects in colon cancer cells versus nontumor colon cells. NB extract increased the accumulation of reactive oxygen species (ROS) and increased endoplasmic reticulum (ER) stress via stimulation of the unfolded protein response. Stress scavengers, N-acetylcysteine (NAC) and 4-phenylbutyric acid (4-PBA), decreased the stress induced by NB. The results showed that NB extract increased ER stress through overproduction of ROS in superinvasive colon cancer cells, decreased their resistance threshold, and produced a nonreturn level of ER stress, causing DNA damage and cell cycle arrest, which prevented them from achieving hyperproliferative capacity and migrating to and invading other tissues. On the contrary, NB extract had a considerably lower effect on nontumor human colon cells, suggesting a selective effect related to stress balance homeostasis. In conclusion, our results confirm that the growth and malignancy of colon cancer cells can be decreased by marine compounds through the modification of one of the most potent resistance mechanisms present in tumor cells; this characteristic differentiates cancer cells from nontumor cells in terms of the stress balance.